Balance in young male soccer players: dominant versus non-dominant leg - Bigoni, M.; Turati, M.; Gandolla, M. (Sport Sciences for Health, 2017)
Purpose: To investigate whether soccer affects the young players` one leg stance balance ability and to understand if balance ability in young soccer players is influenced by age, morphometric parameters or motor coordination capabilities. Methods: Ninety-two male healthy pediatric soccer players aged between 5 and 10 years were enrolled in this study. Sway path, sway area, and sway velocity of center of pressure (CoP) were recorded by means of a strain gauge platform with automatic weight correction. Athletes stood barefoot on firm surface with open eyes alternatively on bipedal condition, dominant or non-dominant foot and with closed eyes on bipedal condition. Morphometric parameters were collected. Gross motor coordination was tested with the Koerperkoordinations Test fuer Kinder (KTK). Results: Better balance outcomes were observed in open eyes and closed eyes bipedal conditions with respect to unipedal ones. Our study shows no differences in dominant and non-dominant single leg stance control. We observed a significant positive correlation of the age with the KTK score. One leg stance on dominant foot demonstrated to be well predicted by age, BMI, and motor coordination capabilities. Non-dominant one leg stance was predicted by BMI and coordinative parameters. Conclusions: Young footballers developed the ability to control in the same way one leg stance on dominant and non-dominant leg. Their postural control is directly influenced by their gross motor coordination for dominant and non-dominant leg, but age influences only dominant leg balance parameters. This supports the hypothesis that balance training should also be introduced in childhood sports training sessions to improve postural control. ABSTRACT FROM AUTHOR